1996
DOI: 10.1073/pnas.93.26.15382
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to inhibition by β-chemokines correlates with biological phenotypes of primary HIV-1 isolates

Abstract: Primary HIV-1 isolates were evaluated for their sensitivity to inhibition by ␤-chemokines RANTES (regulated upon activation, normal T-cell expressed and secreted), macrophage inflammatory protein 1␣ (MIP-1␣), and MIP-1␤. Virus isolates of both nonsyncytium-inducing (NSI) and syncytium-inducing (SI) biological phenotypes recovered from patients at various stages of HIV-1 infection were assessed, and the results indicated that only the isolates with the NSI phenotype were substantially inhibited by the ␤-chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
83
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 46 publications
15
83
2
Order By: Relevance
“…26 In contrast, other investigations of longitudinally followed HIV-1-infected subjects demonstrate that sensitivity to coreceptor and fusion antagonists decreases from the chronic to the late phase of disease. [22][23][24][25] One of the major differences with our study and these previous publications is that we examined variants from the early and chronic phase of infection in a highly characterized seroincident cohort with well-defined dates of estimated seroconversion as opposed to comparing variants from the chronic and late stage of disease. In addition, we observed no significant differences in both PBMC-passaged and 293T-derived nonpassaged recombinant viruses, suggesting that sensitivity changes to CCR5 and fusion blockers were not an artifact from in vitro selection.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…26 In contrast, other investigations of longitudinally followed HIV-1-infected subjects demonstrate that sensitivity to coreceptor and fusion antagonists decreases from the chronic to the late phase of disease. [22][23][24][25] One of the major differences with our study and these previous publications is that we examined variants from the early and chronic phase of infection in a highly characterized seroincident cohort with well-defined dates of estimated seroconversion as opposed to comparing variants from the chronic and late stage of disease. In addition, we observed no significant differences in both PBMC-passaged and 293T-derived nonpassaged recombinant viruses, suggesting that sensitivity changes to CCR5 and fusion blockers were not an artifact from in vitro selection.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to receptor usage changes, HIV-1's sensitivity to various antiretroviral drugs changes over time. We and others have shown that over the course of infection, envelopes have decreased sensitivity to CCR5 receptor and fusion inhibitors, [21][22][23][24][25] although this has not been a universal observation in all subjects. 26 Given the extensive changes observed in both the envelope and polymerase gene, it remains unclear if the sensitivity changes are observed only for entry blockers or also against other drugs from different antiretroviral classes.…”
mentioning
confidence: 99%
“…independent of the sensitivity of their primary isolates to the antiviral effect of the recombinant ␤ chemokine in vitro (54,55), might instead reflect a decreased ability of the CD8 ϩ T cells to produce the antiviral ␤-chemokine MIP-1␣ and MIP-1␤.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 disease progression is not necessarily associated with virus insensitivity to the ␤-chemokine effect (54,55), because 50% of the HIV-1 ϩ subjects who developed AIDS harbor nonsyncytia inducing viruses (56). The loss of viral control in these patients, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First, regulated upon activation of normal T cell expressed and secreted (RANTES), 1 macrophage inflammatory protein-1 ␣ (MIP-1 ␣ ), and macrophage inflammatory protein-1 ␤ (MIP-1 ␤ ), members of the ␤ -chemokine family, were demonstrated to be potent inhibitors of HIV replication in vitro (9), although not all virus strains have been found to be sensitive to this antiviral activity (9)(10)(11). Second, the chemokine receptors CCR5 and CXCR4 (fusin) were shown to be efficient coreceptors for macrophage-tropic and T cell line-tropic strains of HIV, respectively (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%